Cellular lineage origins of spasmolytic polypeptide-expressing metaplasia (SPEM): persistent and intensifying debates - Li, Xiaofeng; Li, Yu; Wu, Lili; Wang, Jingbin; Huang, Guoxin; Rong, Lei; Shen, Wenjuan; Ma, Liang; Zhang, Yang (Frontiers in Oncology, 2025)
Spasmolytic Polypeptide-Expressing Metaplasia (SPEM) is a gastric fundic gland metaplasia resembling deep antral glands, associated with drug injury, Helicobacter pylori (H. pylori), or bile reflux. Early-stage SPEM acts as a reparative response, but if the damaging stimuli persist, the metaplastic changes may become irreversible, raising the risk of gastric cancer development. Traditionally, SPEM arises via passive transdifferentiation of chief cells following parietal cell loss. However, recent lineage tracing and genetic models challenge this, suggesting active depletion of chief cells and involvement of isthmus stem cells also contribute to SPEM development, intensifying debate over its cellular origins. This review synthesizes SPEM’s physicochemical drivers and critically evaluates evidence for the three proposed sources: (1) passive chief cell transdifferentiation (2), active chief cell loss, and (3) isthmus stem cells. Clarifying the heterogeneity in the origin of SPEM is challenging until more specific cell ablation techniques are developed, but timely classification of existing research may be instructive.